Consolationism and comparative African philosophy : beyond universalism and particularism - Agada, Ada; Van Norden, Bryan W. (Bryan William) (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"In this highly original book, Ada Agada responds to the question of how a philosophy can be African and at the same time universally relevant by constructing an original philosophical system that is at once African and universal. Drawing on African forms of thought and conceptual schemes like ethnophilosophy, ubuntu, sage philosophy, négritude, ibuanyidanda philosophy, and ezumezu logic, the author introduces new concepts and conceptual schemes like mood and proto-panpsychism into philosophical vocabulary and weaves them into a coherent and original system that promises to significantly impact contemporary African philosophy. Arguing for intercultural and comparative philosophy as a desirable mode of philosophising in a continually globalising and interconnected world, the book demonstrates the universal applicability of consolationism. This book will be of interest to scholars in the fields of African Studies, intercultural philosophy, philosophy of mind, and existentialism"--
Ethnophilosophy in the African Philosophical Canon -- The Perennial Challenge: Transcending the Universalism-Particularism Divide -- Transcending the Universalism-Particularism Divide -- The Challenge of Consolationism -- The Consolationist System -- On God and Nature -- Homo Melancholicus -- Cross-cultural and Comparative Philosophy as Moral Conversation -- Consolation Philosophy's Challenge to German Philosophy and Western Existentialist Thought -- The Intellectual Love of God in a Comparative Context.
Keywords: Philosophy, African -- 20th century; Philosophy, African -- 21st century; Consolation; PHILOSOPHY / General